THE INVESTIGATION OF THE IMPROVEMENT OF SEVENTH GRADE SCHOOL STUDENTS’ COMMUNICATION SKILLS FROM THE MATHEMATICAL HABITS OF MIND IN THE ENRICHED LEARNING ENVIRONMENT - Ezgi KÖRÜKCÜ (Fırat University, 2019)
The purpose of this study is to investigate the improvement of 7th grade school students’ communication skills in the enriched learning environment. The study was conducted on total 20 students’ studying seventh grade classes of elementary education school located Gungoren town of the Istanbul. Based on the question "How could it be possible for the students to gain the skills of habits of minds?”, the enriched learning environment was designed including worksheets, classroom discussions and student performance-based work. The working group was instructed in the designed learning environment for 13 weeks. Throughout this process, the mathematical habits of mind of the students were assessed through the evaluation forms "The Rubric of Cognitive Habits of Mind". During the evaluation process, answers to the questions in each activity and behaviors of the students reflected in their learning environment were collected as qualitative data. The obtained qualitative data were converted into quantitative data in the form of frequencies as percentage. Quantitative data were also analyzed based on students' responses and their performance in the classroom. According to the research findings after the application of the enriched learning environment, the ratio of students’ using the communication skills increased from 30,9% to 64,2%. When the samples from students’ answers on the activities, work and behaviors in the classroom were examined, the ratio and level of utilization of these skills of the students varied depending on the mathematical topics, the type of skills, and the activity content. It was seen that in general students tend to communication component in a positive way. Accordingly, considering that the enriched learning environment affect communication skills of the students in a positive way, it was offered suggestions to researchers who will study in this subject.